Research on representative stress and fracture ductility of P92 steel under multiaxial creep. (January 2016) - Chang, Yuan; Xu, Hong; Ni, Yongzhong; Lan, Xiang; Li, Hongyuan
Abstract: Creep experiments on both plain and notched specimens were conducted at 650 °C over a stress range of 120–185 MPa. The notch strengthening effect was found to exhibit in notched specimens. By using stress components at the skeletal point, several expressions of representative stress were compared to validate their effectiveness in predicting creep rupture lives of P92 steel under multiaxial stress states. The results showed that Hayhurst representative stress was more suitable for life predictions of P92 steel. In the mean time, the relationship between the fracture ductility and multiaxiality was presented to investigate the influence of the multiaxial stress states on creep rupture behavior of P92 steel. A more reasonable prediction model was proposed, and the validity of the model was verified by experimental data. Graphical abstract: Highlights: Creep experiments on plain and notched specimens of P92 steel were conducted. The extent of notch strengthening effect saturates as notch gets sharper. Hayhurst's model is more effective for life prediction under multiaxial creep. The creep fracture ductility decreases with the multiaxiality increasing. A new model was proposed for more accurate prediction of fracture ductility.